Book Reviews. (1st August 2011) - ,
Abstract : BOOK REVIEWS Genevieve Massard-Guilbaud, Histoire de la Pollution Industrielle: France, 1789-1914 (Bill Luckin) Stephen J. Pyne, America's Fires: A Historical Context for Policy and Practice (Simon Pooley) Stefania Barca, Enclosing Water: Nature and Political Economy in a Mediterranean Valley, 1796-1916 (Harold L. Platt) Marcus Hall (ed.), Restoration and History: The Search for a Usable Environmental Past (Joshua Specht)